Effects of long working hours and shift work during pregnancy on obstetric and perinatal outcomes: A large prospective cohort study—Japan Environment and Children's Study. Issue 1 (31st October 2019) - Suzumori, Nobuhiro; Ebara, Takeshi; Matsuki, Taro; Yamada, Yasuyuki; Kato, Sayaka; Omori, Toyonori; Saitoh, Shinji; Kamijima, Michihiro; Sugiura‐Ogasawara, Mayumi; ,
Abstract: Background: The work patterns of pregnant women may be related to adverse obstetric and perinatal outcomes. This study aimed to clarify the effects of weekly working time according to frequencies of night shifts during pregnancy on adverse outcomes in Japan. Methods: The Japan Environment and Children's Study, a prospective cohort study, was conducted in 15 regions nationwide in Japan. The study population included pregnant women with singleton pregnancies (n = 99 744). The mothers' working hours and frequencies of night shifts during the first and the second/third trimesters were assessed using a self‐administered questionnaire. Outcome data were collected from medical transcripts. Results: Compared with nonworking women, women who worked during pregnancy had significantly increased adjusted odds ratios (aORs) of threatened miscarriage (maximum aOR: 1.47, 95% confidence interval [95% CI]: 1.26‐1.73) and of threatened preterm labor (maximum aOR: 1.63, 95% CI: 1.41‐1.87). Increased aORs were observed for hypertensive disorders of pregnancy (maximum aOR: 2.02, 95% CI: 1.39‐2.93) in women working ≥36 hours per week with night shifts, for vacuum/forceps delivery (maximum aOR: 1.34, 95% CI: 1.22‐1.48) at ≥36 hours with or without night shifts, and for small‐for‐gestational‐age babies (aOR: 1.32, 95% CI: 1.10‐1.59) at ≥46 hours with night shifts. In contrast, lower aORs were observed for gestational diabetes and meconium‐stained amniotic fluid in women working without night shifts. Conclusions: Work during pregnancy slightly increased the risks of threatened miscarriage and threatened preterm labor. Long working hours increased the risks of hypertensive disorders of pregnancy, vacuum/forceps delivery, and small‐for‐gestational‐age babies.